Luminescence and generation of laser radiation in zinc selenide and cadmium sulfide single crystals exposed to high-voltage subnanosecond pulses - Mesyats G. A. Gennady Andreyevich; Nasibov A. S.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2008, 2008)
В фонде НТБ ТПУ отсутствует